Brachial and central blood pressure and arterial stiffness in adult elite athletes - Tomschi, F.; Ottmann, H.; Bloch, W.; Grau, M.; Predel, H.-G. (European Journal of Applied Physiology, 2021)
Purpose: Measures of arterial stiffness (AS) and central blood pressure (BP) are indicators for cardiovascular health and possess a high prognostic value in the prediction of cardiovascular events. The effects of physical training are widely unexplored in the context of competitive, high-performance sports. Therefore, we aimed to present possible reference values of brachial and central BP and of AS of adult elite athletes compared to a control group. Methods: A total of 189 subjects participated in this cross-sectional study. Of these were 139 adult elite athletes (70 male, 69 female) performing on top-national and international level, and 50 control subjects (26 male, 24 female). Resting brachial and central BP and aortic pulse wave velocity (PWV) were measured and were compared in terms of sex, sport category, and age of the athletes. Results: Results show no difference between athletes and controls in any parameter. Women exhibit lower brachial and central BP and AS values compared to men. PWV is positively correlated with age. Evaluation of the parameters according to the different sport categories showed that endurance athletes exhibit lower BP and PWV compared to other athletes. Conclusions: This study presents brachial and central BP and PWV values of athletes, suggesting that high-performance sport does not negatively impact AS. The proposed reference values might support a more detailed evaluation of elite athlete`s cardiovascular and hemodynamic system and a better assignment to possible risk groups.